Safe Harbor Principle, Exclusion of Criminal Liability for Platform Service Providers - Wijayanto, Indung; Wulandari, Cahya; Rasdi, Rasdi (IJCLS (Indonesian Journal of Criminal Law Studies), 2023)
In the era of Society 5.0, characterized by the pervasive digitalization of societal functions, platform service providers play a pivotal role. These platforms, however, are frequently exploited by users for unlawful activities. This study investigates the prerequisites for invoking the safe harbor principle, which shields service providers from criminal liability. Employing a qualitative research approach, secondary data was gathered through a comprehensive literature review and subsequently analyzed qualitatively. The safe harbor principle serves as a critical legal mechanism utilized by platform service providers to shield themselves from legal repercussions arising from illicit actions committed by their users. To qualify for this exemption, providers typically must promptly remove unlawful content upon notification and refrain from active involvement in the transmission of such information. However, recent developments indicate that providers may forfeit safe harbor protection if they play a significant role in moderating or curating content on their platforms.  This research underscores the essential conditions that platform service providers must meet to avail themselves of the safe harbor principle, highlighting the nuanced balance between facilitating digital innovation and upholding legal accountability. By clarifying these conditions amidst evolving regulatory landscapes, this study contributes to ongoing discussions on legal frameworks governing digital platforms, offering insights crucial for policymakers, legal practitioners, and stakeholders navigating the intersection of technology, law, and societal governance.